1992
DOI: 10.1093/brain/115.5.1359
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Reaction Times in Patients With Frontal and Parietal Lesions

Abstract: The effect of unilateral circumscribed lesions in different areas of the frontal and parietal cortex on the distributions of saccadic reaction times (SRTs) was investigated in 32 patients under four stimulus conditions: (i) gap-random: a target light appeared 200 ms after extinction of a central fixation light randomly at 8 degrees either left or right; (ii) overlap-random: like (i), but the fixation light remained on ('overlap'); (iii) gap-simultaneous: two peripheral lights appeared simultaneously left and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(80 citation statements)
references
References 0 publications
7
70
0
3
Order By: Relevance
“…The existence of express saccadeenhanced persistent neurons in LIP supports the findings from lesion study of posterior parietal cortex in human and nonhuman primates in which the number of express saccades decreased and the SRT distribution of regular saccade shifted to the right (Lynch and McLaren, 1989;Braun et al, 1992;Li et al, 1999). Our results also support the findings of a more recent human EEG study in which authors found the increased activity in occipital-parietal network during mid-gap and lategap intervals preceding express saccades (Hamm et al, 2010).…”
Section: Preparatory Activity Plays Crucial Role In Determining Srtsupporting
confidence: 62%
See 1 more Smart Citation
“…The existence of express saccadeenhanced persistent neurons in LIP supports the findings from lesion study of posterior parietal cortex in human and nonhuman primates in which the number of express saccades decreased and the SRT distribution of regular saccade shifted to the right (Lynch and McLaren, 1989;Braun et al, 1992;Li et al, 1999). Our results also support the findings of a more recent human EEG study in which authors found the increased activity in occipital-parietal network during mid-gap and lategap intervals preceding express saccades (Hamm et al, 2010).…”
Section: Preparatory Activity Plays Crucial Role In Determining Srtsupporting
confidence: 62%
“…Notably, this hypothesis excluded the involvement of the higher cortical regions in express saccade generation. In contrast, another line of experiments observed that, following lesions of posterior parietal cortex in both human and nonhuman primates, express saccades were rare and saccade reaction times (SRTs) increased (Lynch and McLaren, 1989;Braun et al, 1992;Li et al, 1999). Consistent with this, EEG studies in humans found increased activity in an occipital-parietal network during the gap interval preceding express saccades (Hamm et al, 2010), further suggesting that parietal areas might be specifically involved in generation of express saccades.…”
Section: Introductionmentioning
confidence: 99%
“…In general, patients with lesions encompassing the FEF seem to have difficulty inhibiting saccades to inappropriate stimuli (Braun et al 1992;Guitton et al 1985;Machado and Rafal 2004a). More specifically for fixation-related inhibition, such patients can show abnormally small fixation-offset effects on their contralesional side (Machado and Rafal 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a recent review has highlighted the predominant role of the parietal eye field in 'reflexive' saccades, and the frontal eye fields in 'voluntary' saccades (Leigh and Kennard 2004). In particular, parietal eye field lesions in humans cause increased latency of visually triggered saccades, which does not seem to occur after frontal eye field lesions (Pierrot-Deseilligny et al 1991;Braun et al 1992). Furthermore, lesion of the parieto-collicular tract can cause isolated impairment of reflexive but not memoryguided saccades (Gaymard et al 2003).…”
Section: The Site Of Action Of Dopaminementioning
confidence: 99%